EFFECT OF PHYTASE SUPPLEMENTATION IN PLANT-BASED FEED ON FEED UTILIZATION AND GROWTH OF Pangasius hypophthalmus DURING THE GROW-OUT STAGE - Rini, Endah Setyo; Rachmawati, Diana; Sarjito, Sarjito (Jurnal Riset Akuakultur, 2024)
Phytic acid, found in many plant-based fish feed ingredients, is an anti-nutritional compound that binds with minerals, forming complexes that fish intestines cannot easily absorb. Adding phytase, an enzyme, to plant-based feeds has shown potential in enhancing nutrient absorption and has been effective for various aquaculture species. However, its impact on Pangasius hypophthalmus, a commonly farmed fish, remains underexplored. This study examines the effects of phytase on feed conversion ratio (FCR), feed utilization efficiency (EFU), protein efficiency ratio (PER), relative growth rate (RGR), and survival rate (SR) of P. hypophthalmus. Fish (average weight 11.55 g) were kept at a density of 40 fish m-³ in a fully randomized design with four treatments (0, 500, 1000, and 1500 FTU kg-1 feed) and three repetitions. Data on RGR, EFU, PER, FCR, SR, and water quality were analyzed. Results indicated that phytase significantly improved RGR, EFU, PER, and FCR (P<0.05), though SR remained unaffected. The optimal phytase dose, 738-810 FTU kg-1 feed, produced an EFU of 69.3% and an RGR of 4.77% per day during the grow-out stage. Water quality parameters remained stable and within optimal ranges across all treatments.Asam fitat, yang ditemukan dalam banyak bahan pakan ikan berbasis tanaman, adalah senyawa anti-nutrisi yang mengikat mineral, membentuk kompleks yang sulit diserap oleh usus ikan. Penambahan fitase, enzim, pada pakan berbasis tanaman menunjukkan potensi dalam meningkatkan penyerapan nutrisi dan telah efektif untuk berbagai komoditas budidaya. Namun, dampaknya pada Pangasius hypophthalmus, ikan yang umum dibudidayakan, masih belum banyak dieksplorasi. Penelitian ini mengkaji efek fitase pada rasio konversi pakan (RKP), efisiensi pemanfaatan pakan (EPP), rasio efisiensi protein (REP), laju pertumbuhan relatif (LPR), dan tingkat kelangsungan hidup (TKH) dari P. hypophthalmus. Ikan (berat rata-rata 11,55 g) dipelihara pada kepadatan 40 ikan m-³ dalam rancangan acak lengkap dengan empat perlakuan (0, 500, 1000, dan 1500 FTU kg-1 pakan) dan tiga ulangan. Data LPR, EPP, REP, RKH, TKH, dan kualitas air dianalisis. Hasil menunjukkan bahwa fitase secara signifikan meningkatkan LPR, EPP, REP, dan RKP (P<0,05), meskipun berpengaruh signifikan terhadap TKH. Dosis fitase optimal, 738-810 FTU kg-1 pakan, menghasilkan EPP sebesar 69,3% dan LPR sebesar 4,77% per hari selama tahap pembesaran. Parameter kualitas air tetap stabil dan dalam rentang optimal di semua perlakuan.